2015
DOI: 10.1007/s10897-015-9876-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Counseling Experiences of Early Adopters of Whole Exome Sequencing

Abstract: Currently, there are limited data regarding the practice of genetic counseling for whole exome sequencing (WES). Improved understanding of how genetic counselors and other providers are educating, counseling, and communicating results may identify practice trends, and patient or provider needs. Between April 2013 and December 2014, we surveyed providers who ordered WES testing from GeneDx, a CLIA-certified laboratory. Forty-nine respondents completed the survey; 41 % of participants reported board certificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…61 Providers felt that recipients' apparent enthusiasm for a wide range of SF—often wider than most programs currently offer—may result from incomplete understanding of the implications of SF. 47 Studies did report highly variable knowledge of WES/WGS among WES/WGS recipients, both potential and actual, 26,27,33,35,43,44,56 and providers' own understanding of SF was highly variable and sometimes insecure, 13,50,55,58,62,63 with implications for informed consent provision.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…61 Providers felt that recipients' apparent enthusiasm for a wide range of SF—often wider than most programs currently offer—may result from incomplete understanding of the implications of SF. 47 Studies did report highly variable knowledge of WES/WGS among WES/WGS recipients, both potential and actual, 26,27,33,35,43,44,56 and providers' own understanding of SF was highly variable and sometimes insecure, 13,50,55,58,62,63 with implications for informed consent provision.…”
Section: Resultsmentioning
confidence: 98%
“…24,49,64 Most providers felt that these discussions should include SF, whereas others variably included which SF would be reported, false-positive/negative results, changing the interpretation of variants, family, and the potential for anxiety. 54,61,62 Discussions are very context-dependent and should be flexible and tailored to the recipient. 45,47,54,56,61 Very recent studies of HCPs' experiences with WES/WGS counseling highlighted often-unrealistic recipient expectations and the need to counteract this.…”
Section: Resultsmentioning
confidence: 99%
“…Factors that increased the time needed for genetic counseling were the participant (or partner) was pregnant at the time of the visit, an increased number of results, and lack of familiarity by the genetic counselors with some of the results. Several previous studies have looked at aspects of time required for genetics services related to GS in other contexts (Arora et al 2016; Sukenik-Halevy et al 2016; Williams et al 2014). However, these studies are substantially different in design and context such that none of these previous reports are easily comparable to the work reported here so direct comparisons are not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (2014) described time for pre-test work ups in a neurodevelopmental clinic, but do not provide data on time for the results disclosure process. The other two studies (Arora et al 2016; Sukenik-Halevy et al 2016) report on retrospective surveys and provide estimates for genetics practice in general rather than specific contexts, such as preconception care. In addition, one of these studies does not clearly break out estimates of genetic counseling time from that of other genetics providers (Arora et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…That being said, few studies have systematically compared the cost and efficacy of exome sequencing with those of traditional testing methods or evaluated the likelihood that exome sequencing would eliminate a diagnostic odyssey if implemented earlier in the diagnostic evaluation (9,125). Despite minimal evidence to support the cost effectiveness of exome sequencing, in a survey of providers who ordered diagnostic exome sequencing for their patients, 74% of the respondents (34 out of 46) indicated that cost effectiveness was one of their reasons for ordering the test (5). More research in this area is warranted to determine whether genome-scale sequencing is an ideal early diagnostic step for all genetic conditions.…”
Section: Exome and Genome Sequencingmentioning
confidence: 99%